The Teaching of Grammar - Cuesta Cuesta, Mª Rosario (Miscelánea: A Journal of English and American Studies, 1995)
The purpose of this paper is to examine a number of theoretical principles concerning the teaching of English grammar in EFL contexts. Section One begins with an examination of the strengths and drawbacks of product and process approaches, arguing that there is no single right methodology for the teaching of grammar and advocating a variable balance between product and process perspectives. Section Two gives recognition to the role of individual differences in learning style. Section Three focuses on the relationship between instruction and second language learning, suggesting that learners require formal instruction and informal exposure and that the two together work better than either on its own. Finally, Section Four considers the role of consciousness-raising in the acquisition of grammatical structure. It examines the question of whether second language learning is conscious or unconscious. While the relevance of unconscious processes should not be ignored, a serious reassessment of the notion of consciousness and its role in language learning is necessary.